2016
DOI: 10.1155/2016/1849162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inositol(s) in Women with PCOS: A Systematic Review of Randomized Controlled Trials

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder, with complex etiology and pathophysiology, which remains poorly understood. It affects about 5–10% of women of reproductive age who typically suffer from obesity, hyperandrogenism, ovarian dysfunction, and menstrual irregularity. Indeed, PCOS is the most common cause of anovulatory infertility in industrialized nations, and it is associated with insulin resistance, type 2 diabetes mellitus, and increased cardiovascular risk. Although insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 42 publications
0
84
1
16
Order By: Relevance
“…The improvement in the lipid profile observed at the end of 24 weeks was as follows; with myo-inositol, triglycerides decreased by 15. 14,15 In about 50% of patients with PCOS, insulin receptor phosphorylation is impaired. Several trials showed that insulin sensitizer agents, such as metformin and MI, are the first-line treatment to restore normal menstrual cycles in women suffering from PCOS [16][17][18] suggesting that an endocellular defect of the precursor of IPG such as MI and/or DCI might trigger the compensatory hyperinsulinemia in most PCOS subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in the lipid profile observed at the end of 24 weeks was as follows; with myo-inositol, triglycerides decreased by 15. 14,15 In about 50% of patients with PCOS, insulin receptor phosphorylation is impaired. Several trials showed that insulin sensitizer agents, such as metformin and MI, are the first-line treatment to restore normal menstrual cycles in women suffering from PCOS [16][17][18] suggesting that an endocellular defect of the precursor of IPG such as MI and/or DCI might trigger the compensatory hyperinsulinemia in most PCOS subjects.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In about 50% of patients with PCOS, insulin receptor phosphorylation is impaired. Several trials showed that insulin sensitizer agents, such as metformin and Myoinositol, are the first-line treatment to restore normal menstrual cycles in women suffering from PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of the presence of a defect in the transduction signal of insulin has focused attention on the function of the second messengers of insulin signals, such as IPG (inositol fosfo glycans). In particular, studies show that a deficiency of myo-inositol can underlie, besides a non-insulin response, also a reduced answer to ovarian FSH, being the myo-inositol the second hormone messenger predisposed to follicular growth [89,90]. Insulin acts as a real gonadotropic hormone in the ovary.…”
Section: Insulin and The Regulation Of Stereoidogenesismentioning
confidence: 99%